Gone in a Splash? Temporal Dynamics of Flukeprint Environmental DNA (eDNA) Detection for Common Coastal Northeast Pacific Cetacean Species - Chloe V. Robinson; Emma Laqua; Amy Migneault; Gary J. Sutton; Karina Dracott; Ashley Bachert (Environmental DNA, 2025)
ABSTRACT Environmental DNA (eDNA) analytical techniques have been developed and applied to a small subset of cetacean species worldwide. Direct or “flukeprint” eDNA sampling has previously been proven as an effective approach for detecting DNA from target cetacean species including harbor porpoises (Phocoena phocoena), humpback whales (Megaptera novaeangliae), and killer whales (Orcinus orca). These common species are under increasing pressure from coastal anthropogenic activities throughout their respective Northeast Pacific ranges, and there is an increasing urgency to employ less invasive tools to address data gaps to inform conservation measures. However, it is unclear how long DNA shed in flukeprints persists for each of these species in the dynamic ocean environment. In this study, we opportunistically collected seawater (2–3 L) from flukeprints when individual harbor porpoise (n = 3), humpback whales (n = 3), and killer whales (n = 3) were observed diving. We collected samples across a series of five time points after each flukeprint was first observed: 30 s, 1 min 30 s, 2 min, 5 min 30 s, and 10 min 30 s. A total of 45 samples were collected across three species and analyzed with previously published species‐specific quantitative PCR (qPCR) assays to assess the persistence of eDNA over time. We found a variation in the detectability across the five time points between both target species and individuals sampled, with a general trend consisting of reduced eDNA detectability over time. These findings yield insights into the temporal dynamics of cetacean eDNA in marine environments, demonstrating the importance of species‐ and context‐specific considerations when designing effective monitoring strategies.